2020
DOI: 10.1021/acs.macromol.0c01862
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive In Situ Detection of Chemical Reactions at the Buried Interface between Polyurethane and Isocyanate-Based Primer

Abstract: Polyurethane potting compounds and sealants, widely used as encapsulating and protective barriers, are usually applied to substrates after precoating substrate surfaces with primers. While the use of primers is known to improve adhesion properties of polyurethanes, fundamental mechanisms of adhesion enhancement are not fully understood due to the difficulties of direct observations at buried interfaces. Interfacial properties like adhesion are determined by interfacial molecular structures. In this study, sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 74 publications
1
31
1
Order By: Relevance
“…Figure displays the SFG spectra collected from the primer surface in the wavenumber region of 2050–2400 cm –1 using the ppp and ssp polarization combinations of the input laser beams and the output signal beam. A distinct peak around 2250 cm –1 was observed in each spectrum, which is assigned to the characteristic NCO stretching signal . In Figure a and b, a noticeable decrease in terms of the intensity of this peak in both the ssp and the ppp spectra was observed from the primer surface with 4-h exposure to the atmosphere compared to that with no atmosphere exposure.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Figure displays the SFG spectra collected from the primer surface in the wavenumber region of 2050–2400 cm –1 using the ppp and ssp polarization combinations of the input laser beams and the output signal beam. A distinct peak around 2250 cm –1 was observed in each spectrum, which is assigned to the characteristic NCO stretching signal . In Figure a and b, a noticeable decrease in terms of the intensity of this peak in both the ssp and the ppp spectra was observed from the primer surface with 4-h exposure to the atmosphere compared to that with no atmosphere exposure.…”
Section: Resultsmentioning
confidence: 87%
“…Our lab previously researched the mechanism of the adhesion enhancement at the interface between an isocyanate-based primer and a polyurethane potting compound . The research confirmed the formation of chemical bonding at the buried primer/potting compound interface, which contributed to the enhanced adhesion performance.…”
Section: Introductionmentioning
confidence: 80%
“…In this research, we applied sum frequency generation (SFG) vibrational spectroscopy to study the molecular structure at the buried graphene/PT interfaces. SFG is a coherent, second-order nonlinear optical spectroscopy that utilizes the chemical selectivity of IR and Raman spectroscopies to detect molecular structures including functional group orientation at a medium where the inversion symmetry is broken. In a typical SFG experiment, a visible laser beam with a fixed frequency and a frequency-tunable IR beam overlap both spatially and temporally at the sample interface where two photons are combined; a third photon with the sum of the two input photons’ energies is generated. According to the selection rules of SFG spectroscopy, only a medium with no inversion symmetry can generate an SFG signal under the electric-dipole approximation. ,,,,, In the bulk environment, most of the polymer molecules are randomly distributed and thus form an isotropic sample that possesses inversion symmetry, which will not generate an SFG signal.…”
Section: Introductionmentioning
confidence: 99%
“…This study used a commercial SFG spectrometer from EKSPLA and all the SFG spectra were collected using ssp (s-polarized sum frequency signal, s-polarized input green beam, and p-polarized IR beam) polarization combinations. [78][79][80] In this work, to collect SFG spectra, right-angle CaF 2 prisms (Altos Photonics, Bozeman, MT) were used as substrates. PI and DIP materials used for SFG study were prepared by dissolving 1 g of the appropriate PDMS and the calculated amount of salt based on stoichiometry in separate 5 mL aliquots tetrahydrofuron (THF).…”
Section: Methodsmentioning
confidence: 99%